Towards a Wind Urbanism in Tropical Environments - Perrau , Antoine (Journal of Architectural/Planning Research and Studies (JARS), 2022)
One of the conditions for the proper functioning of passive comfort in humid tropical environments is access to natural ventilation in buildings. This notion of access to natural ventilation has taken on its full meaning during the current health crisis. Based on this observation established by a rich literature, we asked ourselves how to ensure the sustainability of the good functioning of natural ventilation in a humid tropical environment of a building in a built complex? This questioning led us to show the importance of the context through various dimensions: the chain of natural ventilation, the programmatic context, the climatic and geographical context, the regulatory context. Taking these parameters into account has allowed us, in the context of a case study, the eco-district Cœur de ville de La Possession, on the island of La Réunion, to develop a new conceptual approach associating urban planning and aeraulic engineering from the beginning of the design process for maximum efficiency. To this end, we initiated a new approach based on: co-design, the use of physical wind tunnel simulation at different scales, the integration of environmental, architectural and landscape recommendations at the scale of the district and of the buildings making up this district, in an enforceable urban planning regulation. This has enabled us, within the framework of this eco-district, to develop the concept of the right to natural ventilation, of the windy city and of the guarantee over time of the preservation of this potential. The transcription of this approach in other eco-neighbourhoods in a tropical environment seems to us to be a major challenge to be considered and which could even be extended to other climatic zones, in the context of current global warming.